Juridical Reconstruction and Integration of Restorative Justice Mechanisms: Transformation of Police Peace Agreements into Legally Binding Court Decisions - Bahori Ahoen (Pelopor Publikasi Akademika, 2026)
The evolution of the contemporary criminal justice system in Indonesia is marked by a fundamental shift from a retributive paradigm centered on retaliation and physical punishment toward a restorative justice paradigm that prioritizes victim recovery and social reintegration. This shift has been operationalized through internal legal instruments such as Police Regulation (Perpol) Number 8 of 2021. However, a critical juridical void exists: peace agreements reached at the police investigation stage currently have only the status of private agreements (onderhands), which are administrative in nature and thus lack inherent executorial power. This research report presents an in-depth analysis of the urgency and mechanism of transforming such peace agreements into an Acte van Dading (Deed of Settlement) recognized by the District Court. By integrating police discretionary authority with the court’s civil adjudicatory authority through the “Lawsuit for Confirmation of Peace Agreement” mechanism based on Supreme Court Regulation (PERMA) Number 1 of 2016, the legal system can guarantee legal certainty (rechtszekerheid), close the loophole for re-prosecution through the ne bis in idem principle, and ensure civil execution without new litigation. Through a comparative law approach examining Civil Law and Common Law jurisdictions, as well as the theoretical framework of Therapeutic Jurisprudence, this article argues that this integration is not merely an administrative procedure but constitutes the foundation for sustainable substantive justice